2019
DOI: 10.3917/rfe.183.0127
|View full text |Cite
|
Sign up to set email alerts
|

Les banques centrales peuvent-elles encore être indépendantes ?

Abstract: Cet article discute la notion d’indépendance des banques centrales en s’appuyant sur une analyse critique des fondements du modèle qui s’est imposée dans les années 1990 et en analysant son évolution récente. De fait, les banques centrales sont aujourd’hui fortement impliquées sur les questions de stabilité financière et ont des interactions croissantes avec la politique budgétaire. Nous suggérons alors que l’indépendance des banques centrales n’est pas une condition suffisante pour l’efficacité des politiques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 54 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…Jorda et al (2015) concluded that asset price bubbles are dangerous when they are associated with strong credit growth. Moreover, Blot (2015) rejected the hypothesis that price stability serves FS. From this literature, we note that empirical studies led to mixed results on the effectiveness of monetary policy to prevent FS.…”
Section: Literature Reviewmentioning
confidence: 97%
See 2 more Smart Citations
“…Jorda et al (2015) concluded that asset price bubbles are dangerous when they are associated with strong credit growth. Moreover, Blot (2015) rejected the hypothesis that price stability serves FS. From this literature, we note that empirical studies led to mixed results on the effectiveness of monetary policy to prevent FS.…”
Section: Literature Reviewmentioning
confidence: 97%
“…A second group of studies argued that monetary policy has no effect on FS (Blot, 2015). Laseen and Pescator (2020) concluded that it is not appropriate for the Canadian central bank to use monetary policy to ensure FS via a balance of growth in household indebtedness and house prices.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation